2021
DOI: 10.3390/ijerph19010292
|View full text |Cite
|
Sign up to set email alerts
|

Increased Accessibility to Primary Healthcare Due to Nurse Prescribing of Medicines

Abstract: Since January 2016, nurses and midwives in Poland have had the right, with some restrictions, to prescribe medicines. Consequently, Polish patients received the same opportunity as in other countries worldwide: easier access to certain health services, i.e., medical prescribing. The aim of this study was to assess the impact of structural changes which increased the nurses’ competences on the accessibility to prescription visits for patients receiving primary healthcare on the example of Medical and Diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The number of nurses who issued prescriptions in Catalonia increased from 3604 in 2021 to 5563 in 2022. Similar increases were reported in Poland, where the number of nurse prescriptions increased nearly sixfold, and the number of nurse prescribers doubled [ 34 ]. A retrospective study in Wales also found that the number of prescribing nurses doubled, and the prescriptions increased greatly after implementation in primary care [ 35 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The number of nurses who issued prescriptions in Catalonia increased from 3604 in 2021 to 5563 in 2022. Similar increases were reported in Poland, where the number of nurse prescriptions increased nearly sixfold, and the number of nurse prescribers doubled [ 34 ]. A retrospective study in Wales also found that the number of prescribing nurses doubled, and the prescriptions increased greatly after implementation in primary care [ 35 ].…”
Section: Discussionsupporting
confidence: 74%
“…During the second year, although 85% of the nurse prescriptions issued corresponded to these products, more nurse prescriptions for medication were issued than in the previous year, possibly owing to nurses’ expertise and their demand to expand the catalogue of medications that nurses can prescribe. Other authors have reported a significant increase in nurse prescriptions for medications in patients with chronic disease [ 34 ]. Other studies have also found a preponderance of prescriptions for health products [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…(25) No Brasil, não é exigido ao enfermeiro da APS nenhuma especialização ou mestrado para realizar a prescrição como ocorre em outros países. (4,(22)(23)(24)26,27) No cuidado a pessoa com hipertensão e diabetes é competência do médico estabelecer o diagnóstico e prescrição inicial, sendo atribuição do enfermeiro o monitoramento e a manutenção da prescrição médica. Também competência para instituir o tratamento no caso de ausência do médico e agendar posteriormente a consulta médica, como no caso do protocolo da tuberculose.…”
Section: Introductionunclassified
“…As mudanças estruturais que aumentaram as competências dos enfermeiros levaram a um aumento das consultas com prescrição de medicamentos feitas por enfermeiros entre 2017 a 2019. (27) As práticas de enfermagem individuais e coletivas, exercidas com autonomia dentro dos regulamentos Enferm Foco. 2024;15(Supl 1):e-202404SUPL1 5 locais, promovem melhoria no acesso aos cuidados na APS em áreas de escassez de profissionais de saúde.…”
Section: Introductionunclassified